Comparative analysis of synchromodality in major European seaports - Katrin Brümmerstedt; Hendrik Meyer-Van Beek; Torsten Münsterberg (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
Global container throughput recorded a substantial growth over the past 25 years. The ports of Rotterdam, Hamburg and Antwerp have benefited greatly from this development. At the same time rapid increases can be observed for the dimensions of container vessels calling these ports. In 2005 the average capacity of container vessels in operation between Northern Europe and Far East amounted to 6,000 TEU. Today market actors already talk about container vessels with a capacity of 24,000 TEU. (ITF, 2015) This development provides a challenge for seaports concerning the water-side and landside accessibility. According to UVHH (2014) a rising amount of Ultra Large Container Vessels in the Port of Hamburg bears the risk of an increasing number of peaks and bottlenecks within the container terminals. These fluctuations will be continued at the interface to hinterland transport modes and to the connections to hinterland regions. By intelligently combining and switching between different transport modes the concept of synchromodality could form a solution for improving hinterland transportation and reducing bottlenecks in the seaports. (Tavasszy et al., 2015) This paper analyses the degree of implementation of synchromodality in major European container ports with special focus on the Port of Hamburg.
urn:nbn:de:gbv:830-88217722; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; synchromodality; maritime logistics; Hinterland transport chains; collaborative networks